Antecedents of satisfaction in the emerging digital economy: A case study in an urbanised settting - Salman, Ali; Azman, Hazita; Abdul Razak, Norizan; Hussin, Supyan; Md. Sidin, Samsinar (2013)
The digital economy is the new wave of economy sweeping the world.Countries that have positioned themselves to be active players in the emerging digital economy are said to reap the benefits accruing there from.For the digital economy to move forward, satisfaction is very important.This study aims at determining the antecedents of satisfaction in a digital economy.The study uses a survey where some 514 respondents living in the Klang Valley were randomly interviewed using a standard questionnaire. The data was analysed using SPSS 20.0 and both descriptive and inferential statistics were used.Using multiple regressions, trust, security and ease of use emerge as the only significant variables contributing to the variations in satisfaction.The Adjusted R Squared for satisfaction is.301 meaning the three variables contribute 30.1% of the variations in satisfaction.Trust has the highest beta and t value, hence having the highest effect and impact on satisfaction. Thus, for the smooth and continuous uptake of digital economy, handling these variables seen as antecedents of satisfaction is very crucial.